Hotel Customer Satisfaction: A Comprehensive Analysis of Perceived Cleanliness, Location, Service, and Value - Singgalen, Yerik Afrianto (Forum Kerjasama Pendidikan Tinggi, 2024)
This research investigates the key determinants of customer satisfaction in the hospitality industry, focusing on cleanliness, service quality, location, and value. Analyzing guest reviews, the study reveals that 85% of guests consider cleanliness a primary factor influencing their overall experience, while 78% highlight service quality, particularly staff responsiveness and professionalism, as crucial components. Location is identified as a significant contributor by 65% of guests, emphasizing convenience and accessibility to local attractions, and 72% of guests evaluate their satisfaction based on the perceived value of the stay, which balances price and service quality. Additionally, digital engagement, health and safety perceptions, and sustainability practices play an increasing role in shaping guest satisfaction. Specifically, 60% of guests appreciate digital features such as contactless check-in and personalized communication. Meanwhile, 70% note that visible health and safety measures, including enhanced cleaning protocols, positively impact their comfort and trust. Furthermore, 58% of guests prefer hotels adopting sustainability practices, such as reducing plastic use and promoting eco-friendly amenities. The study concludes that 90% of guests rated cleanliness, service quality, and value highly were more likely to recommend the property and return in the future. In contrast, properties lacking in these areas saw a 45% decline in repeat visit intentions. These findings underscore hospitality providers' need to prioritize these factors and integrate digital, health, and sustainability considerations to optimize service delivery, enhance guest satisfaction, and establish a sustainable competitive advantage.